Harvard Business Review on Managing Health Care - Harvard Business School Publishing Corporation (Harvard Business Review Book, 2007)
As the population ages, the US?s already strained health care system faces the possibility of a life-threatening crisis. At stake are the quality of care for millions of Americans and the financial well-being of individuals and employers squeezed by skyrocketing premiums--not to mention the stability of state and federal government budgets. How can we fix it before it?s too late? HBR lends its wisdom and insight to this collection of articles, which explores the problems endemic to the industry, and demonstrates how we can and should invest in change now.